Population dynamics of Arthroschista hilaralis pest and its parasitoid diversity in various jabon (Anthocephalus cadamba) cropping patterns in South Sumatra, Indonesia - SRI UTAMI; HERMANU TRIWIDODO; PUDJIANTO PUDJIANTO; AUNU RAUF; NOOR FARIKHAH HANEDA (Biodiversitas Journal of Biological Diversity, 2018)
Utami S, Triwidodo H, Pudjianto, Rauf A, Haneda NF. 2018. Population dynamics of Arthroschista hilaralis pest and its parasitoid diversity in various jabon (Anthocephalus cadamba) cropping patterns in South Sumatra, Indonesia. Biodiversitas 19: 239-245. Jabon (Anthocephalus cadamba), a native tree species in Indonesia exhibit natural distribution, spreading over an enormous area in this region. In South Sumatra, jabon has long been cultivated in both communities and industrial plantation forests.  Arthroschista hilaralis (Lepidoptera: Pyralidae) is the most damaging insect pest of jabon in South Sumatra. This study analyzed the population dynamics of A. hilaralis in jabon monoculture and two agroforestry systems, and assessed the diversity of the pest parasitoids and their parasitism level on A. hilaralis. Our results showed that planting systems, climatic factors, and the presence of parasitoids could significantly affect the population dynamics of A. hilaralis; its mean population density was highest in monocultures plantation during the rainy season compared with population densities in agroforestry systems. Three parasitoids species attacking A. hilaralis were found in these agroforestry systems, including Phanerotoma sp.,  Apanteles sp. and Brachymeria sp., while only one species (Apanteles sp.) was found in a monoculture. The rate of parasitization of  A. hilaralis within agroforestry systems was higher than in monocultures, and the level of larval parasitization by Apanteles sp. in the agroforestry system was higher in instar 1 than in other larval stages.